Participatory involvement of farming communities and public sectors in determining malaria control strategies in Mvomero District, Tanzania - Mlozi, MRS; Shayo, EH; Senkoro, KP; Mayala, BK; Rumisha, SF; Mutayoba, B; Senkondo, E; Maerere, A; Mboera, LEG (Tanzania Journal of Health Research, 2009)
No Abstract.